Molecular Signatures of Lithium Treatment: Current Knowledge - Bellivier, Frank; Marie-Claire, Cynthia (Pharmacopsychiatry, 2018)
Lithium (Li) is the key mood stabilizer in the prevention of mood recurrences and suicide in bipolar disorders. However, only one-third of patients become asymptomatic with Li treatment, and to date, no clinical markers can predict this response variability. Li is a multitargeting drug, complicating an understanding of its mechanisms of action. The present article reviews Li’s various biological effects, including those obtained in transcriptomic and epigenetic studies, in both humans and animal models. A molecular signature of the therapeutic response to Li is urgently required, including possibly from the circulation. This would better clarify the therapeutic mechanism of Li’s action as well as the development of clinical biomarkers. As such, the biological underpinnings of Li’s beneficial effects should provide clearer understanding of the varying pathophysiological processes in bipolar disorder presentations, with implications for classification and clinical management, possibly leading to a personalized prescription.
Keywords: Bipolar disorder treatment; lithium; biomarker of response